2019
DOI: 10.1101/755504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A lipid code-dependent phosphoswitch directs PIN-mediated auxin efflux in Arabidopsis development

Abstract: 18 19 Directional intercellular transport of the phytohormone auxin mediated by PIN FORMED (PIN) 20 efflux carriers plays essential roles in both coordinating patterning processes and integrating 21 multiple external cues by rapidly redirecting auxin fluxes. Multilevel regulations of PIN activity 22 under internal and external cues are complicated; however, the underlying molecular mechanism 23 remains elusive. Here we demonstrate that 3'-Phosphoinositide-Dependent Protein Kinase1 24 (PDK1), which is conserved… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…5g,h) suggest that phospholipids are part of the auxin transport-controlling regulatory pathway. Most likely they are necessary for the PM association of PAX and of other AGC1 clade kinases 34 downstream of PDK1. Moreover, since the PDK1S0 isoform is clearly more active than full-length PDK1 in auto-and transphosphorylation in vitro (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5g,h) suggest that phospholipids are part of the auxin transport-controlling regulatory pathway. Most likely they are necessary for the PM association of PAX and of other AGC1 clade kinases 34 downstream of PDK1. Moreover, since the PDK1S0 isoform is clearly more active than full-length PDK1 in auto-and transphosphorylation in vitro (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8m-o). In a parallel study, Tan and co-workers showed that reduced lateral root initiation is caused by lack of activation of the PDK1 substrates D6PK/ D6PKLs 34 . This indicates that PAX has a very specific role in vascular development.…”
Section: Crispr/cas9-generated Mutant Alleles Indicate a Central Role For Pdk1 In Developmentmentioning
confidence: 99%